Limited edition : prototypes, one-offs and design art furniture - Lovell, Sophie (Birkhauser, 2009)
Limited edition is the new buzzword in furniture design. This title pursues this new trend in furniture design and uncovers its background in meticulous investigative essays based on the author's ongoing interchange with designers, gallery owners, and manufacturers